Investigasi Energi Termal pada Mesin Diesel Tipe SULZER ZAV 40S dengan Bahan Bakar Marine Fuel Oil (MFO) - Marcelina, Marcelina; Khairi, Syahrul; Kurniawan, Eddy; P Yolanda, Kristina Desideria (UNISTEK, 2021)
The study of thermal energy produced by the Sulzer ZAV 40S diesel engine using Marine Fuel Oil (MFO) can affect the engine combustion process because of the change in fuel chemical energy into internal work. The heat energy generated in the diesel engine where the ignition process when the piston approaches the dead point is then followed by the presence of fuel, namely MFO. The fuel will be sprayed through the nozzles into the combustion chamber. This will result in a complete combustion process where the composition of the mass of air and fuel in the cylinder will generate heat due to the high temperature. The results of the calculation that the need for fuel and air to produce the energy value (Q) of this diesel engine is 808.33 Kcal and the power (Ni) is 4,602.09 PK in every second while the mass of MGO is 5 Kg and air is 130 Kg in every minutes for continuous rotation of 500 rpm.